Proportional population models and stability analysis on time scales - Yar, Ayse Cigdem; Yilmaz, Emrah (Walter de Gruyter Gmbh, 2025)
The study of changes in population size and reasons for these changes appear as population dynamics. These dynamics generally focus on change in population size over time. Mathematical modeling is used to make sense of these changes. In this study, three population models have been reconstructed and solved using proportional derivative on time scales. Equilibrium points and stability states of these solutions were examined.
Keywords: Time scale; proportional derivative; stability